COMMUNITY PERCEPTIONS OF THE SOCIAL PROBLEMS OF WOMEN WHO ARE PREGNANT OUTSIDE OF MARRIAGE - WILDAN HALID (Universitas Islam Negeri Mataram, 2023)
In this research, the author examines the community's perception of the social problems of pregnant women out of wedlock in the Temanggung community. The reason for the research is because of the increasing number of incidents in the village. In the research, the author used the field research method and case studies. The findings in the research were very surprising because, from the samples taken, almost all people considered this to be something normal. This is where the government's role is expected to be to educate the public through the program that is being promoted, namely the anti-merariqkodeq movement, or GAMAQ for short. The conclusions obtained in this research are as follows: 1. The social problems of women who are pregnant out of wedlock start with the deviant behavior of today's teenagers, so that it can lead to early marriages resulting from cases of pregnancy out of wedlock. 2. Meanwhile, regarding public perceptions regarding pregnant women out of wedlock in general, the Lembar community views this case as something that is commonplace, even though this is not in accordance with Islamic law for reasons that can harm the woman, tarnish her, and damage the good name of the family. This fact is in accordance with the results obtained in the field, which show that pregnant women out of wedlock are considered a normal and common occurrence among teenagers today.